Mild Traumatic Brain Injury: What We Can Learn from a Qualitative Study of Patient Perceptions Following Emergency Department Discharge - Kate Ziqiu Wang; Marcia Ward; John Macfarlane (University Library System, University of Pittsburgh, 2022)
Aims: This study investigated the experiences of patients with mild traumatic brain injury (mTBI) to identify barriers and suggest clinically relevant areas for improvement in the current system of care. Methods: 16 patients with a clinical diagnosis of mTBI were recruited from the Cork University Hospital Emergency Department (ED) for participation in this study. Semi-structured phone interviews were conducted at approximately 2.5-3 months post-discharge. Reflexive thematic analysis with an inductive and realist approach was used to code and inductively analyse the data. The most frequently occurring themes and their relationship to subthemes are reported. Results: A total of 16 mTBI adult patients were interviewed (mean age: 50.5 (18-85)). Major themes identified in the experience of mTBI patients were: lack of clarity in diagnosis and treatment, poor access to information, and ongoing symptoms. Notably, 87.5% of participants reported being uncertain about their diagnosis of mTBI and 93.8% of participants did not seek further information regarding their head injury. Nearly half (43.8%) of the participants reported prolonged recovery with two participants (12.5%) reporting ongoing symptoms. Headache, photophobia, and difficulty with thinking and memory were the predominant symptoms reported. Conclusion: Several overarching themes were identified in the qualitative self-reported experiences of mTBI patients following ED discharge. Participants reported persistent symptoms, lack of clarity, and a lack of access to information regarding their mTBI diagnosis and treatment. Suggested recommendations for future practice include adding psychoeducational resources and increasing awareness and training among staff to provide timely patient education.